2015
DOI: 10.3892/ol.2015.4031
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the overexpression of Yin Yang 1 and the expression levels of miRNAs in Burkitt's lymphoma: A computational study

Abstract: A growing number of studies have highlighted the role of microRNAs (miRNAs or miRs) in the development and progression of cancer. In particular, the aberrant expression of cancer-related proteins, such as oncogenes and tumor suppressors has been shown to correlate with the modulation of the expression of specific miRNAs. In the present study, we aimed to determine which downregulated miRNAs may be involved in modulating the expression of the oncogenic transcription factor, Yin Yang 1 (YY1). YY1 has been report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 44 publications
3
37
0
Order By: Relevance
“…OncomiR or Onco-suppressor role Hematological cancers OncomiR or Onco-suppressor role [91][92][93][94][95][96][97][98][99][100][101][102][103][104][105]…”
Section: Solid Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…OncomiR or Onco-suppressor role Hematological cancers OncomiR or Onco-suppressor role [91][92][93][94][95][96][97][98][99][100][101][102][103][104][105]…”
Section: Solid Tumorsmentioning
confidence: 99%
“…The role of miR-181a and b in Lymphoid cell development has been reviewed by Guarini et al [62], and specific expression profiles linked to the different steps of the maturation/differentiation process largely documented [103,104]. In a recent study, it has been shown that miR-181b directly down-regulates the expression of FAMLF (Familial acute myelogenous leukemia related factor) and inhibits cell viability by binding to the 5 UTR of FAMLF in Burkitt Lymphomas (BL), allowing the authors to suggest a new mechanism of the pathogenesis of BL, and to propose miR-181b as a candidate therapeutic agent in BL forms with FAMLF overexpression [62].…”
Section: Lymphomamentioning
confidence: 99%
“…In particular, the two latter epigenetic events are now been recognized as key mechanisms of neoplastic transformation and a plethora of diseases (12,87,150). In this context, recent studies have identified different miRNAs, a class of non-coding RNA of 20-22 nucleotides, associated with the development and progression of different tumors (151)(152)(153)(154)(155)(156)(157). In addition, numerous studies have demonstrated the presence of a dual relationship between microbiota and host microRNAs (miRNAs) and vice versa (158)(159)(160).…”
Section: Possible Mechanisms Of Carcinogenesis Induced By Dysbiosismentioning
confidence: 99%
“…International Journal of Genomics two microRNAs that targeted YY1 mRNA in Burkitt's lymphoma using miRNA target prediction tools and Pearson correlation. The two microRNAs were related to the expression of YY1 and downregulated in Burkitt's lymphoma [42]. Using two public available GEO datasets, Falzone et al reported several microRNAs that were associated with the epithelial-mesenchymal transition pathway and NGAL/MMP-9 pathways in bladder cancer [43]; the author also found four microRNAs which were related to colorectal cancer through the mismatch repair pathway and other tumor signaling pathways [44].…”
mentioning
confidence: 99%